2002
DOI: 10.1001/archpsyc.59.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Olanzapine in Combination With Valproate or Lithium in the Treatment of Mania in Patients Partially Nonresponsive to Valproate or Lithium Monotherapy

Abstract: Background: A 6-week double-blind, randomized, placebo-controlled trial was conducted to determine the efficacy of combined therapy with olanzapine and either valproate or lithium compared with valproate or lithium alone in treating acute manic or mixed bipolar episodes.Methods: The primary objective was to evaluate the efficacy of olanzapine (5-20 mg/d) vs placebo when added to ongoing mood-stabilizer therapy as measured by reductions in Young Mania Rating Scale (YMRS) scores. Patients with bipolar disorder (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
213
6
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 398 publications
(237 citation statements)
references
References 20 publications
13
213
6
5
Order By: Relevance
“…Nine participants met criteria for a current manic episode (Young Mania Rating Scale score X20) and seven were classified as hypomanic (Young Mania Rating Scale score ¼ 12-15;Tohen et al, 2002). The majority of patients were taking mood stabilizers and/or atypical antipsychotics with the most common medication being valproate and lithium or risperidone, respectively.…”
Section: Participantsmentioning
confidence: 99%
“…Nine participants met criteria for a current manic episode (Young Mania Rating Scale score X20) and seven were classified as hypomanic (Young Mania Rating Scale score ¼ 12-15;Tohen et al, 2002). The majority of patients were taking mood stabilizers and/or atypical antipsychotics with the most common medication being valproate and lithium or risperidone, respectively.…”
Section: Participantsmentioning
confidence: 99%
“…As well, a study comparing responders to lithium and lamotrigine identified robust differences with respect to clinical course, comorbid conditions, and family history; 103 and patients nonresponsive to lithium may respond well to olanzapine. 140,141 Finally, genetic research may benefit from growing knowledge of the mechanisms of action of moodstabilizing drugs. This includes the possibility of biochemical endophenotypes as well as informed selection of candidate genes.…”
Section: Response To Long-term Treatmentmentioning
confidence: 99%
“…There is little data regarding the efficacy of atypical antipsychotic medications in aged BP patients. Although newer agents such as aripiprazole may have particular advantages in elders, the broadest experience for mixed-age BP patients relates to risperidone and olanzapine as adjunct therapy [98,99] or as monotherapy [100]. Risperidone, olanzapine, quetiapine, aripiprazole, and ziprasidone have US Food and Drug Administration-approved indications for use in BP disorder.…”
Section: Pharmacodynamic Drug-drug Interactionsmentioning
confidence: 99%